Implications of municipal wastewater irrigation on soil health from a study in Bangladesh. (8th July 2013) - Mojid, M. A.; Wyseure, G. C. L.; Davidson, Donald
Abstract This study evaluated soil health in fields of wheat (Triticum aestivum L. cv Shatabdi) and potatoes (Solanum tuberosum L.) irrigated by different blends of municipal wastewater (hereafter called wastewater). The crops were grown with and without added fertilizers over three consecutive years. The wastewater contained high concentrations of organic carbon (C), nitrogen (N), phosphorus (P), sodium (Na), potassium (K), calcium (Ca), magnesium (Mg), sulphur (S), zinc (Zn) and boron (B). It also contained negligible concentrations of a few heavy metals. Irrigation by wastewater resulted in an increase in the porosity of the surface soil and thus a reduced bulk density. Wastewater enhanced the saturated hydraulic conductivity and water retention capacity of the soils. The organic carbon, total N, available P and S, and exchangeable Na, K, Ca and Mg of the soils increased proportionately with the quantity of applied wastewater. C, N and K increased significantly (α = 0.05) when fields were irrigated using raw wastewater after applied fertilizers; the other elements accumulated in the soil insignificantly under both fertility levels. Electrical conductivity (EC) and pH of the upper 0–20 and 20–40 cm soil layers increased with the application of wastewater; the increase was significant only under raw wastewater irrigation. In the 40–60 cm soil layer, both EC and pH remained unchanged. The applied inorganic fertilizers raised EC but reduced soil pH. The wastewater contained large counts of total coliform (TC: 17.2 × 106 cfu/100 mL) and faecal coliform (FC: 13.4 × 103 cfu/100 mL). Irrigation using municipal wastewater is proposed for improving soil fertility as well as for alleviating water scarcity with the exception of some crops whose edible parts come in direct contact with wastewater and/or are eaten uncooked.